2013
DOI: 10.1111/ahe.12045
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging ( MRI ) Spinal Cord and Canal Measurements in Normal Dogs

Abstract: The goal of this study was to establish Magnetic resonance imaging (MRI) reference ranges for spinal measurements in normal dogs. Forty dogs (1–10 kg, 11–20 kg, 21–30 kg, > 30 kg; 10 dogs per category) underwent spinal MRI. Measurements were performed on sagittal T2-W images at the level of the 4th thoracic vertebra (T4), the 9th thoracic vertebra (T9) and the 3rd lumbar vertebra (L3). Spinal canal diameter (mm) ranged from 6.07 ± 0.63 (1–10 kg) to 8.27 ± 1.15 (> 30 kg) at the level of T4; 6.55 ± 0.61 (1–10 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 19 publications
1
34
0
1
Order By: Relevance
“…Dog breeds were included if acceptable MRI studies (minimum of 5 animals per breed) were available for the study period. The limited number of dogs in this study ( n = 44) is similar to other comparable studies (11, 12). …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Dog breeds were included if acceptable MRI studies (minimum of 5 animals per breed) were available for the study period. The limited number of dogs in this study ( n = 44) is similar to other comparable studies (11, 12). …”
Section: Discussionsupporting
confidence: 85%
“…A canine cadaver study, comparing spinal canal and spinal cord measurements on T1 and T2 weighted images on MRI to the actual specimen, showed improved correlation of T2 weighted imaging and anatomical measurements compared to T1 weighted images (12). Consequently in our study, T2 weighted images were used to evaluate vertebrae and disks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they appear to be more painful than do dogs with thoracolumbar IVD extrusions . Several investigators have suggested that these observations may be a consequence of anatomic differences with respect to the size of the epidural space, presumably resulting in less severe mechanical damage to the cervical than to the thoracolumbar spinal cord …”
Section: Discussionmentioning
confidence: 99%
“…There are substantial anatomic differences between the cervical and thoracolumbar vertebral columns, including the IVD. The vertebral canal in the cervical vertebra has a larger diameter than in the thoracolumbar vertebra, leaving more epidural space around the spinal cord . In dogs, the thoracic IVD is narrower than the cervical IVD, and the cervical IVD is nearly circular in shape when viewed craniocaudally, whereas the thoracic disks are more oval and the lumbar disks bean‐shaped .…”
mentioning
confidence: 99%